Exploring the Impact of Madrasah Head's Leadership Style on Teacher Performance - Muhammad Taufiqurrahman; Ahmad Ridani; Sudadi Sudadi (Nurul Jadid University, 2025)
This study is motivated by the demands of the reform era, which emphasizes the improvement of education quality through the strategic role of the madrasah principal not only as a manager but also as a visionary leader capable of creating a conducive work environment and promoting teacher professionalism. The participatory and Islamic-oriented leadership style at the madrasah is considered to have a positive impact on teachers’ enthusiasm and sense of responsibility. This research uses a quantitative correlational approach with survey instruments to determine the extent to which leadership style influences teacher performance. The results show that the principal’s leadership style has a very significant effect on teacher performance, with a contribution of 88.5%. In comparison, the remaining 11.5% is influenced by other factors not examined in this study. These findings emphasize the crucial role of leadership style in enhancing teacher performance and the overall quality of education at madrasah.